In vitro susceptibility testing for the emerging pathogenic mould Veronaea botryosa and pharmacokinetic parameters of natamycin in white sturgeon (Acipenser transmontanus) - Coleman, Denver (Journal of fish diseases, 2022)
© 2022 John Wiley & Sons Ltd.